In Vitro Release of Metformin HCl from Polyvinyl Alcohol (PVA) - Gelatin Hydrogels Prepared by Gamma Irradiation - H Hariyanti; E Erizal; E. Mustikarani; I. Lestari; F. Lukitowati (Atom Indonesia, 2022)
The aim of this present work is to use polyvinyl alcohol (PVA) – gelatin-based  hydrogel prepared by γ-rays irradiation with different gelatin concentrations ranging from 0.5 - 2 %w/v for immobilization of Metformin HCl (MH) at dose range of 0 - 30 mg. The mixture were freezed-thawed for 3 cycles, irradiated using  γ-rays with sterilization dose at 25 kGy (dose rates 5 kGy/h). Gel fraction and water absorption were determined gravimetrically. The surface morphology of hydrogels were observed using Scanning Electron Microscope (SEM). In vitro release of MH were taken using UV-Vis spectrophotometer. After evaluated, it was found that with increasing gelatin concentrations, gel fraction increases and water absorption decreases. With increasing gelatin concentration and drug dosage, the cumulative drug released decreases. From SEM observation, the hydrogel had a heterogeneous porous. The hydrogel based on PVA-gelatin can be considered as a matrix for controlled drug release and safe for humans since both PVA and gelatin are non-toxic.